Measurement of MMP-7 in micro-volume peripheral blood: development of dried blood spot approach - Jingying Jiang; Shuyang Liu; Min Du; Jiale Deng; Gong Chen; Yifan Yang; Rui Dong; Zhuo Fang; Shan Zheng (Frontiers Media S.A., 2023)
PurposeSerum matrix metalloproteinase-7 (MMP-7) is significant in differentiating biliary atresia (BA). This study aims to develop a new peripheral blood quantitative collection device to detect MMP-7 levels via dried blood spot (DBS).MethodsThis is a diagnostic accuracy test. Serum and DBS MMP-7 concentrations were measured using an ELISA kit. Intraoperative cholangiography and subsequent histological examinations were used to confirm BA diagnoses.ResultsA total of 241 infants with obstructive jaundice were enrolled, among whom 168 were BA. Linear regression showed DBS MMP-7 correlated well with serum MMP-7 (R = 0.93, P < 0.001). The best cut-off value of serum MMP-7 for BA was 25.9 ng/ml, achieving the area under the ROC curve (AUC) of 0.962 (95% CI: 0.941, 0.983), and the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were 86.9%, 94.5%, 97.3% and 75.8%, respectively. The best cut-off value of DBS MMP-7 for BA was 12.5 ng/ml, achieving the AUC of 0.922 (95% CI: 0.888, 0.956), and the sensitivity, specificity, PPV, and NPV were 86.9%, 89.0%, 94.8%, and 74.7%, respectively. The dried blood spots were intervened under different storage conditions, including 1-5 days at room temperature, 2 or 3 days at 30 °C and 2 or 3 days at 37 °C. The DBS MMP-7 concentration under different storage conditions had good correlation and consistency with that at −80 °C.ConclusionsSerum and DBS MMP-7 correlate well, both of which have high accuracy in the diagnosis of BA, while the requirements for the storage of DBS are low.